Implementation of lean manufacturing in the spinning industry to increase production efficiency - Parmawati, Sih; Nugraheni, Dyah Novia; Kurniati, Edy Dwi; Darmawi, Ahmad; Alwi, Muhammad (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
The spinning industry is an important part of the textile sector that faces efficiency challenges due to the large amount of waste in the production process. This study aims to analyze the implementation of Lean Manufacturing as a strategic approach to improving production efficiency in one of the medium-scale spinning companies in West Java. Using a qualitative descriptive method, data were obtained through direct observation, in-depth interviews with six key informants, and analysis of company documents. The results of the study indicate that the application of Lean principles such as 5S, Just-In-Time (JIT), Total Productive Maintenance (TPM), and Visual Management can reduce waiting time between processes by 55%, reduce the frequency of machine breakdowns by 62.5%, and increase the orderliness of the work area by 68%. Even so, the implementation of lean is not free from challenges such as the mismatch of production schedules with machine readiness, resistance to work culture from senior employees, and lack of in-depth understanding of lean tools. This study confirms that the success of Lean Manufacturing depends not only on the tools used, but also on the readiness of the organizational culture and supporting information systems. These findings provide practical contributions to the development of efficient and sustainable operational management strategies in the spinning industry, and offer recommendations in the form of integrated training, integration of production information systems, cross-departmental evaluation, periodic lean audits, and performance-based reward schemes.